Byron and Weltliteratur - Halmi, N (Edinburgh University Press, 2018)
The ageing Goethe was fascinated with Byron whom he called the greatest poetic talent. Though suspicious of Byron’s Philhellenism, Goethe found in Byron an openness to encounter non-English cultures, an attentiveness to national histories and in interest in the relationship of the individual to social life. Byron’s self-contextualising, self-historicising narrative poems constitute a parallel to Goethe’s own literary campaigns for cross-cultural engagement in the 1810s and 1820s and, despite Byron’s alienation from England, offer hope for the prospects of what Goethe was to call “world literature”.